LEGAL PROTECTION OF UNREGISTERED MARKS IN INDONESIA - Harwanto, Edi Ribut; Arifin, Samsul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
In accordance with Law No. 20 of 2016 pertaining to Marks and Geographical Indications, trademark protection in Indonesia is only granted following registration under a constitutive system. This study aims to examine the pseudo-legal protection afforded to unregistered trademark owners in Indonesia. This study employs a normative legal research methodology because its focus departs from the ambiguity of norms, employing a statute approach and a conceptual approach. The technique for tracing legal materials involves document analysis techniques and qualitative study analysis. The findings of this study indicate that Mark Protection in Indonesia is granted only after registration in accordance with the constitutive registration system adopted by Law No. 20 of 2016 regarding Marks and Geographical Indications. Unregistered trademarks are not protected by law. Meanwhile, if an unregistered mark is used or imitated without permission or rights, the owner of the mark cannot file a lawsuit against the violator.